Distance comparisons in virtual reality: effects of path, context, and age - van der Ham, Ineke J. M.; Baalbergen, Heleen; van der Heijden, Peter G. M.; Postma, Albert; Braspenning, Merel; van der Kuil, Milan N. A. (Frontiers in Psychology, 2015)
In this large scale, individual differences study (N=521), the effects of cardinal axes of an environment and the path taken between locations on distance comparisons were assessed. The main goal was to identify if and to what extent previous findings in simple 2D tasks can be generalized to a more dynamic, three-dimensional virtual reality environment. Moreover, effects of age and gender were assessed. After memorizing the locations of six objects in a circular environment, participants were asked to judge the distance between objects they encountered. Results indicate that categorization (based on the cardinal axes) was present, as distances within one quadrant were judged as being closer together, even when no visual indication of the cardinal axes was given. Moreover, strong effects of the path taken between object locations were found; objects that were near on the path taken were perceived as being closer together than objects that were further apart on this path, regardless of the metric distance between the objects. Males outperformed females in distance comparison, but did not differ in the extent of the categorization and path effects. Age also affected performance; the categorization and path effects were highly similar across the age range tested, but the general ability to estimate distances does show a clear pattern increase during development and decrease with aging.